2018
DOI: 10.21608/jabps.2018.4088.1016
|View full text |Cite
|
Sign up to set email alerts
|

An overview on the chemical and biological aspects of lycorine alkaloid

Abstract: Amaryllidaceae plants are currently appreciated as a plentiful source of unique bioactive alkaloids. Among them, lycorine is one of the major pyrrolophenanthridine alkaloids commonly isolated from different species of this family. Over the past years, lycorine has attracted great research interest owing to its superlative biological potential and pharmacological actions, including antitumor, antiangiogenic, antiviral, antibacterial, antimalarial, anti-parasite, antioxidant, hepatoprotective, analgesic, anti-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…Crude endophyte extras of Bacillus safensis , Pseudomonas cichorii , and Arthrobacter pascens displayed the presence of lycorine, and this is not surprising as endophytes can metabolize secondary metabolites from the host plant [ 104 ]. Lycorine has been reported to possess antibacterial activity and cytotoxic and antitumor activities [ 95 ]. This would explain the observed antibacterial and/or anticancer activity of the crude endophyte extracts.…”
Section: Resultsmentioning
confidence: 99%
“…Crude endophyte extras of Bacillus safensis , Pseudomonas cichorii , and Arthrobacter pascens displayed the presence of lycorine, and this is not surprising as endophytes can metabolize secondary metabolites from the host plant [ 104 ]. Lycorine has been reported to possess antibacterial activity and cytotoxic and antitumor activities [ 95 ]. This would explain the observed antibacterial and/or anticancer activity of the crude endophyte extracts.…”
Section: Resultsmentioning
confidence: 99%
“…Previous phytochemical studies on C. asiaticum reported that alkaloids, coumarins, glycosides, triterpenes, phenolics, and flavonoids are constituents of C. asiaticum leaf [ 27 , 28 ]. Lycorine is one of the major Crinum alkaloids [ 14 , 28 ]. A previous study reported that ethanolic extract of the leaves exerted in vitro anti-inflammatory activity by the inhibition of nitric oxide production [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…NO, one of the inflammatory mediators important in the inflammation process which have a destructive effect on articular cartilage, helps bring about osteoarthritis which is the most common chronic degenerative disease. Additionally, lycorine has potent immunological, antitumor, and anti-inflammatory activities [ 14 , 15 ] and has been shown to decrease autophagy in osteoclasts in vivo [ 16 ]. Therefore, lycorine is most likely the responsible active compound in C. asiaticum extract thus supporting the traditional use of C. asiaticum in the mitigation of joint pain.…”
Section: Discussionmentioning
confidence: 99%
“…Galanthamine is used for the treatment of Alzheimer’s disease [ 1 ]. Lycorine possesses the ability to inhibit in vitro replication of the poliomyelitis virus, herpes simplex virus, Bunyamwera virus, West Nile virus, dengue virus and Severe Acute Respiratory Syndrome-Coronavirus (SARS-CoV) [ 2 , 3 , 4 , 5 ]. This alkaloid also exhibits antimalarial [ 6 ] and cytotoxic activities, which have led to clinical trials to determine the use of lycorine in the treatment of cancer [ 7 ].…”
Section: Introductionmentioning
confidence: 99%